HUMAN RIGHTS AND EDUCATIONAL REALITY - Quirós Vargas, Emilia (2019)
The article presents a reflection on Costa Rican education with a focus on human rights. In addition to educational inclusion, issues of diversity and educational quality are analyzed, as well as the requirements for educational acceptability and the aspects in which the educational system is in deficit. It considers demands and challenges that make the country face the urgent need to make greater efforts, developing plans, programs and projects in the light of human rights.